Strategy for Internalizing Islamic Character Values through the Dhuha Prayer Program: A Qualitative Study at SMK Muhammadiyah Salaman - Khasanah, Safiratul; Novita, Novita Aristawati; Purnomo (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Moral degradation among Indonesian youth necessitates effective strategies for internalizing Islamic character values, especially in vocational schools that face challenges in balancing spiritual and technical education. This study analyzes the internalization strategies of Islamic character values through the shalat dhuha program at SMK Muhammadiyah Salaman. Using a descriptive qualitative approach, data were collected through interviews and document analysis, then analyzed using Miles and Huberman’s interactive model with triangulation for validation. The study identifies key internalized values such as discipline, responsibility, honesty, and spirituality. Implementation involves a holistic strategy through daily habituation, the 5S cultural model (Smile, Greet, Salute, Politeness, Courtesy), integration of religious curriculum, and structured monitoring. Supporting factors include strong institutional commitment, capable educators, and sufficient facilities, while inhibiting factors involve students' diverse backgrounds and limited awareness of character education. As a result, a strategic model is proposed, comprising: (1) an Islamic-Muhammadiyah philosophical foundation, (2) habituation-based daily practices, (3) a collaborative support system, and (4) continuous evaluation. This model effectively strengthens students’ Islamic character and can serve as a reference for other Islamic-based vocational institutions aiming to implement comprehensive and sustainable character development programs.